2017
DOI: 10.1007/s00253-017-8131-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential application of waste whey as a medium component for Kluyveromyces lactis cultivation and a co-feeder for lipase immobilization by CLEA method

Abstract: Currently, much attention is paid to technologies which can be drivers of the circular economy across different sectors, in particular, to develop technologies for utilization or reusability of biocompatible materials from industrial waste. One of such is the milk whey, which is a cheap biobased raw material, the disposal of which is a major problem for the dairy industry. Our proposed and investigated technology is based on a continuous exploitation of the whey combining microbiology and biotechnology. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…4. The soluble enzyme completely loses activity after incubation for 1 h, whereas the immobilized BGL reserves its initial activity nearly 70% after incubation for 3 h and approximately 50% for 5 h. It has been proved that enzyme immobilized by CLEAs caused it more stable and catalyzed efficiently at high temperature [30]. Stable support-bound BGL could be applied for the enzyme immobilization with economical matrix [31].…”
Section: Thermostability and Reusabilitymentioning
confidence: 99%
“…4. The soluble enzyme completely loses activity after incubation for 1 h, whereas the immobilized BGL reserves its initial activity nearly 70% after incubation for 3 h and approximately 50% for 5 h. It has been proved that enzyme immobilized by CLEAs caused it more stable and catalyzed efficiently at high temperature [30]. Stable support-bound BGL could be applied for the enzyme immobilization with economical matrix [31].…”
Section: Thermostability and Reusabilitymentioning
confidence: 99%
“…CLEA preparation is very simple, it is initialized by the protein precipitation induced by the addition of a precipitant like salts, organic solvents, or polymers, followed by the chemical crosslinking with a bifunctional or poly‐functional agent . CLEAs of several enzymes including many lipases have been reported . However, few studies about CLEAs of pancreatic lipases have been reported (Table ) .…”
Section: Introductionmentioning
confidence: 99%
“…Nosúltimos anos, visando minimizar a formação de produtos indesejáveis durante os processos reacionais e, em geral, atender aos conceitos da química verde, a utilização de lipases em processos industriais tem sido fortemente encorajada em substituição aos processos químicos convencionais [10,11]. Entretanto, os altos custos envolvidos e as dificuldades operacionais para produção e utilização destas enzimas, frequentemente, limitam seu uso [12]. A fim de solucionar os problemas supracitados, e outros interesses, estudos envolvendo lipases vêm apresentando elevado crescimento.…”
unclassified